Pengaruh Kesadaran Wajib Pajak, Pelayanan Fiskus, Sanksi Wajib Pajak, Pemahaman Wajib Pajak, Dan Sikap Rasional Terhadap Kepatuhan Wajib Pajak Orang Pribadi(Studi Empiris Pada WPOP Pribadi di KPP Pratama Surakarta sampai tahun 2016) - Tika, Miss Yuniastuti; , Dra. Mujiyati, M.Si (2016)
Taxpayer compliance which still lower, there was many factor causing for example lowering understanding the most taxpayer about tax; lowering taxpayer perception and tax officer service still lower, taxpayer awareness which still less, and rational attitude of taxpayer. This research was aim to give the empirical evidence was existence of influence taxpayer awareness, understanding of taxpayer, taxation sanction, fiscus services, and rational attitude to taxpayer compliance in KPP Pratama Surakarta. These researches represent the empirical research by using survey method. Primary data obtained from questioner disseminated to taxpayer. Sum up the sampel research counted 100 respondents taken by accidental sampling. The data technique analyse was using the multipllied linear regression analysis. Based on data analysis result could be conclusion that taxpayer awareness, understanding of taxpayer, taxation sanction, fiscus services, and rational attitude was an influence to taxpayer compliance in KPP Pratama Surakarta, this matter can be showed by each variable p value <0,05. So those hypotheses from H1 until H5 have an effect.